2017
DOI: 10.1155/2017/1494538
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Predicting Favorable Outcome of Percutaneous Epidural Adhesiolysis for Lumbar Disc Herniation

Abstract: Background. Lower back pain is a common reason for disability and the most common cause is lumbar disc herniation. Percutaneous epidural adhesiolysis has been applied to relieve pain and increase the functional capacity of patients who present this condition. Objectives. In this study, we retrospectively evaluated the factors which predict the outcome of percutaneous epidural adhesiolysis in patients who were diagnosed with lumbar disc herniation. Methods. Electronic medical records of patients diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 53 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Based on the search criteria, 13 manuscripts were identified and considered for inclusion [ 18 , 25 , 31 - 41 ]. A total of 6 studies met the inclusion criteria [ 25 , 31 , 33 , 37 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the search criteria, 13 manuscripts were identified and considered for inclusion [ 18 , 25 , 31 - 41 ]. A total of 6 studies met the inclusion criteria [ 25 , 31 , 33 , 37 , 38 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 6 manuscripts meeting inclusion criteria [ 25 , 31 , 33 , 37 , 38 , 40 ], there was only one placebo-controlled RCT [ 25 ]. Appendix Tables 4 and 5 show the methodologic quality assessment and risk of bias of the one RCT utilizing the Cochrane review criteria and the IPM-QRB criteria respectively [ 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, axial cut image at the pathological level is given sole priority by the MSU classification system which is periodically practiced by authors around the world to optimize management strategies for patients with lumbar disc herniations. 2 , 10 – 12 The concept of considering a single axial cut image at the level of maximal herniation may be unlike the “Lumbar disc nomenclature: version 2.0” where sagittal images are taken into consideration; 13 even so, the MSU classification clearly defines the shape, location and extent of the disc herniation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to obvious masses and canal narrowing, microscopic adhesions, which may be a result of chronic inflammation, can interrupt the spread of drugs. Although numerous studies have described PEN procedures, only a few have reported intraoperative findings that indicate the surgical outcomes [ 11 , 13 , 14 , 17 19 ]. Epidurography is always performed during PEN procedures, but there is insufficient evidence supporting the usefulness of this procedure.…”
Section: Introductionmentioning
confidence: 99%